MARKETING RESEARCH ON THE ROLE OF EDUCATION IN THE ECONOMIC DEVELOPMENT OF THE COUNTRY - L. Nedykhalov; N. Kharchenko (Вестник Северо-Кавказского федерального университета)
The article discusses various aspects of the dependence of human capital formation on the economy and its development, as well as a marketing analysis and comparison of existing global trends in this area. The solution of new strategic tasks should be based on the development of human potential, which is primarily provided by the development of education. Within the framework of such an important concept, an equally significant factor in itself is considered - the development of the Institute of education and its accessibility to the General population. At the end of the publication, the authors concludes that human capital, its systematic acquisition, accumulation and renewal are directly related to the trends of the country s economic recovery.